The Digital Content on Social Media for Tourism Promotion of Wang Krod Community, Phichit - Chumnumwat, Songpol; Chanvichai, Kittima (Journal of Business, Innovation and Sustainability (JBIS), 2024)
The research titled "The Digital Content on Social Media for Tourism promotion of Wang Krod Community, Phichit" aims to study the factors for planning digital content communication on social media for promoting community tourism in Wang Krod community, Phichit. This study employs a qualitative research approach, utilizing in-depth interviews with individuals involved in managing tourism promotion and public relations through the community's social media channels. Additionally, participant observation, accompanied by note-taking, and the examination of documents and research related to Wang Krod community were conducted. The study's findings indicate that the development of digital content communication planning on social media for promoting community tourism in Wang Krod community, begins with the cultural elements of the community, such as foods, traditions, architecture, and lifestyle. These elements are compiled and developed into digital content, which can be utilized in planning social media communication. This content serves as information for tourists and target audiences, enabling them to study and plan their travels or engage in tourism activities within the community effectively. The process of disseminating community content must include the following communication planning steps: 1) Analyzing the community's situation to identify strengths, weaknesses, opportunities, and threats (SWOT) 2) Defining the appropriate target audience 3) Setting clear objectives to ensure the target audience responds to the content 4) Selecting suitable communication tools and media for the target audience 5) Allocating a budget and timeline for communication 6) Evaluating the results. Moreover, the community should incorporate its culture and events into the content communication plan before publishing on social media. Effective communication of content on social media is crucial for promoting the tourism industry. Well planned and engaging content can foster participation, attract consumer interest, and influence travel decisions. Coupled with efficient use of communication technology, this approach not only attracts tourists but also contributes to the sustainable development of community tourism.